Explaining Algeria’s Nationalist Foreign Policy on the Western Sahara Conflict - Mourad Aty, Abdelhak Elaggoune e (Africana Studia, 2020)
Many analysts assert that Algeria’s support for the Polisario and their aim of independence from Morocco is a policy by Algeria to become either the important hegemon in the Maghreb or to get other strategic gains in the area. Contrary to this view, the present paper argues that the Algerian stance towards the Western Sahara problem since 1975 is less a struggle for hegemony than a practice of one of its ideological principles that distinguish its revolutionary foreign policy. It is the principle of self-determination and extensive support to oppressed peoples everywhere in the world, a trend deeply embedded in its political culture. It also argues that the underlying national and historical values which shaped and continue to shape Algeria’s foreign policy towards the Polisario problem appeared under previous Algerian administrations and are likely to emerge under any future government. Keywords: Algeria, Morocco, self-determination, Western Sahara.